Liquidity in the Liquidity Crisis: Evidence from Divisia Monetary Aggregates in Germany and the European Crisis Countries - Makram El-Shagi; Logan Kelly (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
While there has been some debate over the usefulness of monetary aggregates, there has been surprisingly little discussion of the actual implications for liquidity. In this paper, we provide an approximation of the liquidity development in six Euro area countries from 2003 to 2012. We show that properly measured monetary aggregates contain significant information about liquidity risk.
Keywords: C43; E40; G01; 330